Threat-Avoidance Tendencies Moderate the Link Between Serotonin Transporter Genetic Variation and Reactive Aggression - Peeters, Deborah G. A.; Lange, Wolf-Gero; von Borries, A. Katinka L.; Franke, Barbara; Volman, Inge; Homberg, Judith R.; Verkes, Robbert-Jan; Roelofs, Karin (Frontiers in Behavioral Neuroscience, 2020)
The short (S) allele of the serotonin transporter-linked promoter region (5-HTTLPR) polymorphism has been linked to reactive aggression in men, but this association is less consistent in females. Reactive aggression has been particularly described as a result of fear-driven defense to threat, but how this interaction between defensive behavior and aggression is expressed in S-allele carriers remains unknown. In order to explore this interplay between 5-HTTLPR genotype, defensive behavior and reactive aggression, we combined genotyping with objective measures of action tendencies towards angry faces in an approach-avoidance task (AAT) and reactive aggression in the Taylor aggression paradigm (TAP) in healthy females, N=95. This study shows that female S-allele carriers in general display increased implicit reactive aggression (administering aversive white noise) towards opponents. Furthermore, we found that threat-avoidance tendencies moderate the association between 5-HTTLPR genotype and aggression displayed on the TAP. Together, these findings indicate a positive correlation between avoidance of angry faces in the AAT and reactive aggression in the TAP exclusively present in S-allele carriers.